ANALISIS PENGARUH BRAND TRUST TERHADAP BRAND SUSTAINABILITY PADA BRAND GRACIOUS SPORTWEAR - Yahtadi, Fauzan; Dirgantari, Puspo Dewi (Universitas Dian Nuswantoro, 2025)
This study shows that brand trust plays a crucial role in supporting brand sustainability at Gracious Sportwear. Through transparency, community engagement, and strategic partnerships, Gracious successfully builds consumer trust, strengthens emotional connections, and demonstrates a commitment to sustainability and innovation. The brand has engaged consumers through social media and provided clear information about products and operational policies. Partnerships with local manufacturers also support the economy and the environment, reinforcing social sustainability. However, there are opportunities to increase transparency, expand community involvement, and establish more strategic partnerships to strengthen market positioning. The limitations of this study include the narrow scope of data and its focus solely on Gracious Sportwear, which may not be fully generalizable. Future research is recommended to expand the scope and types of data used for more comprehensive results.